2017
DOI: 10.3390/s17061277
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Activity Trackers for Senior Citizens: Research Perspectives, Commercial Landscape and the Role of the Insurance Industry

Abstract: The objective assessment of physical activity levels through wearable inertial-based motion detectors for the automatic, continuous and long-term monitoring of people in free-living environments is a well-known research area in the literature. However, their application to older adults can present particular constraints. This paper reviews the adoption of wearable devices in senior citizens by describing various researches for monitoring physical activity indicators, such as energy expenditure, posture transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 185 publications
(226 reference statements)
0
72
0
1
Order By: Relevance
“…It is reported in [77] that 35% of non-institutionalized adults had abnormal gait and that sleep disturbances are very common among older people. Further, chronic conditions affect physical activity levels, and activities such as rising from a chair is demanding for older people [77]. It is clear that the whole motion pattern changes with age and the onset of illnesses related to the human locomotor system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported in [77] that 35% of non-institutionalized adults had abnormal gait and that sleep disturbances are very common among older people. Further, chronic conditions affect physical activity levels, and activities such as rising from a chair is demanding for older people [77]. It is clear that the whole motion pattern changes with age and the onset of illnesses related to the human locomotor system.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, none of the studies within Gait and fall, or Stress and sleep have reported that the studies were conducted with patients. Also [76,77] have previously discussed the shortcoming of not conducting studies with patients in the category Gait and fall. Considering the research question for this review article, we question the fact that 35% of the retrieved articles lack information on whether the participants were healthy or patients.…”
Section: Discussionmentioning
confidence: 99%
“…As far as GPS are concerned, their uses enable trajectory reconstruction [ 68 , 98 , 99 , 100 ] hence their usefulness in some cases (to correlate the data measured by the inertial sensors with the mapping of the movement of the participants in their environment). Tedesco et al [ 48 ] review identifies certain types of GPS sensors that can be found in studies tracking activity but mixing up free environments (semi-FLEs and FLEs) with controlled environments. GPS tracking is sometimes used in studies in order to visualise the walking bouts or walking habits of participants.…”
Section: Sensorsmentioning
confidence: 99%
“…De Bruin et al [ 46 ], Byrom and Rowe [ 47 ] (COPD patients), Tedesco et al [ 48 ], Murphy [ 49 ], de Oliveira Gondim et al [ 50 ], and Frechette et al [ 51 ] considered the use of wearable systems (accelerometers or other motion sensors) to monitor activities in specifically targeted cohorts (PD, Multiple Sclerosis (MS)). Vienne et al [ 19 ], Yang and Hsu [ 52 ], and Tedesco et al [ 48 ] also focused on the use of wearable sensors in clinical settings, but considered any kind of cohort. Attal et al [ 53 ] and Narayanan et al [ 54 ] analyzed articles related to activity classification algorithms and classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor unit is a portable module placed on the patient's chest. Accelerometer-and gyroscope-based physical monitoring systems have been shown to be able to discriminate between different daily activities [39][40][41][42]. Each of these physical activities leads to a different level of energy expenditure, and in patients under LTOT, to different oxygen flow requirements.…”
Section: Sensor Unitmentioning
confidence: 99%